Does Pollution Hinder Urban Competitiveness? - Kahn, Matthew E. (World Bank, Washington, DC, 2019)
This paper surveys the recent literature exploring the causes of urban pollution in the developing world and the implications of such pollution for a city's competitiveness. Within a system of cities, cities compete for jobs and people. Those cities that specialize in heavy industrial activity will gain from a manufacturing boom but are more likely to be polluted than a city that specializes in the service economy and one that makes investments in regulations to reduce the social costs of power generation, transportation, and household services. The paper explores three main questions. First, why does pollution inhibit urban competitiveness? Second, why is this effect likely to grow in importance over time? Third, why have cities been slow to adopt cost-effective regulatory strategies?